Pengaruh Literasi Keuangan dan Financial Technology Terhadap Perilaku Keuangan dengan Niat Berperilaku Sebagai Variabel Mediasi pada UMKM di Kota Malang - Amalia Agustin Hidayanti; Muhammad Sulhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of financial literacy and financial technology on financial behavior through behavioral intentions as a mediating variable. This study uses a quantitative method with an explanatory research type. Sampling was carried out using a purposive sampling technique with a method that focuses on MSME actors in Malang City. This study was conducted statistically using the SmartPLS 4.0 analysis tool. Analytical findings show that financial literacy has a positive and significant effect on the behavior and behavioral intentions of MSMEs in Malang City. While financial technology has a positive but insignificant effect on financial behavior. In addition, behavioral intentions are proven to be an important relationship that connects financial literacy and financial technology with financial behavior, emphasizing the crucial role of intentions in supporting better financial management. This study provides recommendations for improving financial literacy and adoption of financial technology among MSMEs to encourage sustainable economic growth.